2020
DOI: 10.1002/cbin.11532
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin‐resistant osteosarcoma cell‐derived exosomes confer cisplatin resistance to recipient cells in an exosomal circ_103801‐dependent manner

Abstract: Studies have shown that exosomes can mediate the chemoresistance of drug‐resistant cells by transmitting circular RNAs (circRNAs). However, the role of exosome‐derived hsa_circ_103801 (exosomal hsa_circ_103801) in osteosarcoma (OS) remains unclear. The level of hsa_circ_103801 was upregulated in the serum exosomes from patients with OS, and OS patients with high hsa_circRNA_103801 expression had a shorter survival time relative to patients with low hsa_circ_103801 expression. The expression of hsa_circ_103801 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…Exosome-mediated circRNAs transfer is another mechanism of CDDP resistance of OS. Pan et al [63] found hsa_circ_103801 was significantly higher in the serum exosomes from OS patients than that in the serum exosomes from healthy controls. The higher expression of hsa_circ_103801 in serum exosomal was correlated with shorter survival in OS patients.…”
Section: Osteosarcomamentioning
confidence: 97%
“…Exosome-mediated circRNAs transfer is another mechanism of CDDP resistance of OS. Pan et al [63] found hsa_circ_103801 was significantly higher in the serum exosomes from OS patients than that in the serum exosomes from healthy controls. The higher expression of hsa_circ_103801 in serum exosomal was correlated with shorter survival in OS patients.…”
Section: Osteosarcomamentioning
confidence: 97%
“…Pan et al showed that exosomes from cisplatinresistant cells (CDDP) reduced the sensitivity of MG63 and U2OS cells to CDDP, inhibited cell apoptosis, and increased the levels of multidrug resistance-related protein 1 and P-glycoprotein expression [87]. In addition, exosomal hsa_circ_103801 could enhance the promoter function of exosomes and promote the chemoresistance of MG63 and U2OS cells to CDDP [87]. Wei et al found that the prepared doxorubicin-loaded exosomes could be used as an excellent chemotherapeutic drug for the treatment of osteosarcoma in vitro [88].…”
Section: The Application Of Evs In Bone Sarcoma Treatmentmentioning
confidence: 99%
“…Studies have confirmed that the level of circRNAs was significantly enriched in exosomes compared to exosome-derived cells. 75 The circRNAs also play a critical role in the progression of ESCC. Fan et al validated circRNA has-circ-0001946 and has-circ-0043603 secreted by ESCC cells might be potential diagnostic biomarkers for ESCC.…”
Section: Exosomal Circrnasmentioning
confidence: 99%